Women and children`s rights in Zamdia: A case study of the Chisungu Initiation Ceremony in the Bemba Community - Mwanamwambwa, Adaobi Tebuho (My University, 2013)
The thesis deals with the conflict between international human rights norms relating to women and children`s rights, and customary practices at a local level. This conflict is examined in the context of the Chisungu Initiation Ceremony practiced by the Bemba community in Northern Zambia. It further examines the various strategies employed by th Zambian Government, and Ngo`s in utilizing human rights standards in efforts to counter customary practices that entrench women and children`s subordination. The thesis deals with critiques of the Universal Paradigm of international human rights law, and contrasts it with Cultural Relativist perspectives. The report, specifically, highlights critiques of the Universalist bias of international human rights norms as compared to the more community based notions of rights and duties in traditional communities sucha s the Bemba. Of particular interest is the thesis analysis and assessment of various counter-hegemonic strategies in attempting to inculcate awareness of women and children`s rights amongst members of the Bemba community